Metastatic papillary craniopharyngioma: Case study and study of tumor angiogenesis - (:unkn) unknown (CARDEN JENNINGS PUBL CO LTD, 2002)
We report a case of suprasellar papillary craniopharyngioma metastatic to the temporoparietal region 2 years after its initial resection. The literature documents examples of craniopharyngioma recurrences along the surgical tract, as well as remote ipsi- and contralateral metastases via cerebrospinal fluid seeding. Ours is the second report of a craniopharyngioma of papillary type to exhibit metastatic behavior. The tumor spread opposite the side of craniotomy. Although a rare occurrence, it confirms the limited capacity of histologically benign craniopharyngiomas to undergo meningeal seeding, likely the result of surgical manipulation. Immunohistochemical demonstration of increased microvascular density and vascular endothelial growth factor expression, as well as a high vascular endothelial growth receptor (VEGFR2) signal by in situ hybridization, suggests that tumor vascularity facilitated angiogenesis and may have been involved in the establishment and growth of the metastatic deposit.
Keywords: GROWTH-FACTOR VEGF; EXPRESSION; RECURRENCE; FEATURES; CHILDREN; ADULTS